A Study on Physico-Chemical Characteristics of Water in Wetlands of Hebbe Range in Bhadra Wildlife Sanctuary, Mid Westernghat Region, India - Raghavendra Gowda, H.T.,, Pramod, A.F., Vijaya Kumara* and (Journal of Experimental Sciences, 2011)
A systematic study has been carried out to evaluate physico chemical characteristics of the selected wetlands of the Bhadra Wildlife sanctuary from May 2009 to April 2010. Three major wetlands which come across the temperate zone of the sanctuary have been selected for the study. Seventeen physico-chemical water quality parameters have been analyzed for pre, post and monsoon seasons. Idan ban kere has a less Catchment area compared to the other two. The pH of the water was found to be more alkaline in Idan ban kere compared to the others. The values of DO and BOD fluctuate according to the seasons and sectors, COD was very less due to absence of chemical pollution. The value of all the parameters are found to be more during pre monsoon season when compared to monsoon and post monsoon in Idan ban kere with comparison to Heggarna kere and Gonimara hadla kere, due to their differences in the catchment area and occurrence of high amount of rainfall during monsoon. Other parameters such as calcium, magnesium, sulphate and phosphate were under permissible limits and widely fluctuated according to seasons and sectors.